Physiological dose response of coffee (Coffea arabica L.) plants to glyphosate depends on growth stage - de Carvalho, Leonardo Bianco; da Costa Aguiar Alves, Pedro Luis [UNESP]; Bianco, Silvano [UNESP]; De Prado, Rafael (Inst Investigaciones Agropecuarias, 2012)
Glyphosate is the main herbicide used in coffee (Coffea arabica L.) plantations in Brazil. Problems with herbicide drift commonly occur in orchard fields due to non-adequate spraying conditions. A series of experiments was carried out aiming to evaluate physiological dose-response of C. arabica plants submitted to exposure to simulated glyphosate drift in two distinct plant growth stages. Glyphosate was applied at 0, 180, 360, and 720 g acid equivalent (AE) ha(-1) directly on coffee plants with 10 and 45 d after transplanting (DAT). Glyphosate doses in a range of 180-360 g AE ha(-1) increased photosynthesis, transpiration and stomatal conductance in 10 DAT-plants up to 14 d after application (DAA) while, in 45 DAT-plants, an increase was observed only up to 2 DAA, but this pattern was not persistent afterwards so that no difference in gas exchange was observed at 60 DAA in both plants. Macronutrient content was not affected by glyphosate application in both plants. Plant DM accumulation was not affected by glyphosate application at 10 DAT-plants, but an increase in plant growth was observed when glyphosate was applied in a range of 360-720 g AE ha(-1) in 45 DAT-plants. Coffea arabica cv. Catuai Vermelho IAC-144 responded differentially to glyphosate drift depending on plant growth stage, regarding on photosynthesis, transpiration, stomatal conductance, and plant growth, in spite of macronutrient nutrition was not affected.

Glifosato es el principal herbicida utilizado en las plantaciones de café (Coffea arabica L.) en Brasil. Problemas con la deriva de herbicidas comúnmente ocurren en los campos de cultivo debido a condiciones no adecuadas de pulverización. Una serie de experimentos se llevó a cabo con el objetivo de evaluar la relación dosis-respuesta fisiológica de plantas de C. arabica expuestas a situaciones simuladas de exposición a deriva de glifosato en dos etapas distintas de crecimiento de las plantas. El glifosato se aplicó en dosis de 0, 180, 360, y 720 g equivalentes ácido (AE) ha-1 directamente en las plantas de café a los 10 y 45 d después del trasplante (DDT). Dosis de glifosato en un rango de 180-360 g AE ha-1 , aumentaron la fotosíntesis, la transpiración y la conductancia estomática en plantas con 10 DDT hasta 14 d después de la aplicación de glifosato (DAA), mientras que en plantas con 45 DDT se observó un aumento sólo hasta 2 DAA, pero no fue persistente, de modo que no se observó diferencia en el intercambio de gases a los 60 DDA en ambas plantas. El contenido de macronutrientes de las plantas a los 10 DDA no fue afectado por las épocas de aplicación de glifosato. La acumulación de MS a los 10 DDA no fue afectada por la aplicación de glifosato, pero a los 45 DDA se observó un aumento del crecimiento de las plantas con glifosato en dosis de 360-720 g AE ha-1. Coffea arabica cv. Catuaí Vermelho IAC-144 respondió de forma diferente a la deriva de glifosato en función de la etapa del crecimiento de las plantas, con respecto a fotosíntesis, transpiración, conductancia estomática, y crecimiento de las plantas, a pesar que la nutrición en macronutrientes no se vio afectada.
Respuesta fisiológica de plantas de café (Coffea arabica L.) a glifosato depende de la etapa de crecimiento
Keywords: Coffea arabica; N-(phosphonomethyl)glycine; herbicide drift; photosynthesis; Plant nutrition